Penerapan Teori Adaptasi dan Inovasi dalam Dakwah pada Pengembangan UKM Center di Desa Sumbermulyo oleh PT. Bumi Suksesindo (BSI) - Mahmudin, Nurudin (Maddah: Journal of Advanced Da'wah Management Research, 2024)
The background of this research lies in the challenges faced by rural communities, such as poverty, limited access to technology, and low economic literacy, which require holistic interventions encompassing economic, social, and spiritual aspects. Da'wah plays a crucial role in inspiring entrepreneurs to be more disciplined, creative, and innovative. This study aims to analyze the application of Adaptation and Innovation Theory in Da'wah for the development of the SME Center in Sumbermulyo Village by PT. Bumi Suksesindo (BSI). This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis. The results indicate that the SME Center successfully implemented digital marketing strategies via Instagram, although the potential of other platforms like TikTok remains underutilized. Collaboration between the SME Center, the government, and other institutions has strengthened business sustainability. The integration of da'wah values proved effective in enhancing the capacity and market reach of local SMEs. Additionally, the SME Center played a vital role in creating social impacts, such as improving living standards and generating employment opportunities. Despite these achievements, challenges like limited resources and information access persist. These findings highlight the importance of leveraging digital technology and fostering strong collaboration among the private sector, communities, and the government to support SME sustainability.